(3QSGdI aj MUhd GdCTcGd GdYGQVI ddchGcH aj MQcGJgGs - (3Ydj Hf bOGeI GdHZOGOj, CHh GdMSfs
(3ChdgG (B:s
(3CeG HYO MeOkG ddg JYGdi Ydi fYe GdSGHZ agPg QSGdI MUhd GdCTcGd GdYGQVI ddchGcH ai MQcGJgG s
(3BNQgG (B:s
(3MUhdgG ef GdJbGhje ddCjGe Ef Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3HGdcJGH GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
(3cJHNGfI edi edc (B(640) s
Keywords: (3Gdadcs